Uses of music in everyday life - North, Adrian; Hargreaves, David; Hargreaves, J. (University of California Press, 2004)
The value of music in people’s everyday lives depends on the uses they make of it and the degree to which they engage with it, which are in turn dependent on the contexts in which they hear it. Very few studies have investigated people’s experiences of music in naturalistic, everyday circumstances, and this exploratory study provides some initial normative data on who people listen with, what they listen to (and what their emotional responses to this music are), when they listen, where they listen, and why they listen. A total of 346 people who owned a mobile phone were sent one text message per day for 14 days. On receiving this message, participants were required to complete a questionnaire about anymusic they could hear, or had heard since their previous message. Responses indicated a high compliance rate; a high incidence of exposure to music; that the greatest number of musical episodes occurred while participants were on their own; that pop music was heard most frequently; that liking for the music varied depending on who the participant was with, where they were, and whether they had chosen to be able to hear music; that music was usually experienced during the course of some activity other than deliberate music listening; that exposure to music occurred most frequently in the evening, particularly between 10PM and 11 PM, and on weekends; that music was heard most frequently at home, with only a small number of incidences occurring in public places; that the importance of several functions of music varied according to temporal factors, the place where the music was heard, and the person or people the participant was with. Further research shouldinclude participants from a greater range of sociodemographic backgrounds and should develop context-specific theoretical explanations of the different ways in which people use music as a resource.